FEATURES CORRELATION INDICATORS RHEOVASOGRAPHY OF THIGH AND SHIN WITH ANTHROPOMETRIC PARAMETERS OF A BODY IN HEALTHY GIRLS WITH DIFFERENT SOMATOTYPE - Сергета, І.В.; Височанський, О.В.; Черепаха, О.Л. (World of Medicine and Biology, 2015)
Aim of our work - to establish differences in connections indicators of rheovasography (RVG) femur and tibia with anthropometric, somatotypological and component indicators of body mass in healthy urban girls with different somatotypes.Materials and methodsFor the study were selected 108 practically healthy girls, in the third generation residents of Podolsk region of Ukraine. Anthropometric survey of adolescents was conducted in accordance with the scheme of Bunak; somatotype determination by the method of J. Carter and B. Heath. Established next somatotypes distribution among the studied girls: mesomorph - 31; ectomorph - 50; ectomesomorph - 20. Визначення компонентного складу маси тіла проводили за методиками J. Matiegka, крім того м’язового компонента за Американським інститутом харчування, а жирового – за Siri.Rheovasography hips parameters determined by computer diagnostic complex, which provides simultaneous registration of ECG, phonocardiograms, basic and differential tetrapolar rheogram and blood pressure measurement. We determined the basic impedance, length of the ascending and descending parts of rheovasography, duration of fast and slow blood supply; notch amplitude, rapid blood filling, diastolic and systolic wave; dicrotic and diastolic indices; average speed of fast and slow blood supply; indicators tone of arteries of various sizes and ratios tone of arteries.Statistical analysis of the results conducted in statistical package license "STATISTICA 5.5" using nonparametric methods. Analysis of correlation obtained results was performed using the statistical method of Spearman.Results. DiscussionsBetween the RVG indicators of hip and anthropo-somatotypological body parameters set the greatest number of reliable feedback: between indicators across time and TSFF (mesomorph) and transverse dimensions of the body (ectomorph); derivatives indicators and transverse (ectomorph) and covering body size (ectomorph, ecto-mesomorph); and between indicators RVG of shin and anthropo-somatotypological body parameters: direct connections - between temporal indicators and width of distal epiphysis limb (WDEL), TSFF (mesomorph) and feedback - between amplitude parameters and covering body size, TSFF (mesomorph); between derivatives indicators and covering body size (mesomorph) and between derivatives indicators and TSFF and components of somatotype (ecto-mesomorph).Between the hip RVG indicators and anthropo-somatotypological parameters body found no reliable connections: between the base impedance and longitudinal body size (mesomorph and ectomorph), TSFF (mesomorph), covering body size (ecto-mesomorph); between amplitude indicators and total body size and body weight components (ecto-mesomorph); between derivatives indicators and total body size (mesomorph); and between RVG of shin and anthropo-somatotypological parameters of body - between the base impedance and somatotype components (mesomorph, ectomorph, ecto-mesomorph), total body size and components of body weight (ectomorph), transverse dimensions of the body (ecto-mesomorph); between indicators across time and total body size and somatotype components (ectomorph), between amplitude indicators and total, longitudinal, covering, cross body size, WDEL and somatotype components (ectomorph).In girls with different somatotypes set opposite reliable connections (for the indicators RVG of hip – direct, and for RVG of shin - return): between dicrotic index and TSFF on the forearm and under the shoulder blade (mesomorph); between amplitude of notch and TSFF on the front of the shoulder and hip (ectomorph); and vice versa for the reverse indicators RVG of thigh, and for RVG indicators of shin - direct: between derivatives indicators and components of body mass and indicators across time and TSFF (mesomorph); between derivatives and total indicators, longitudinal body size and between dicrotic index and WDEL of hip (ecto-mesomorph).
Keywords: rheovasography; correlation; thigh; shin; healthy girls somatotype